Microcalorimetric monitoring of growth of Saccharomyces cerevisiae: osmotolerance in relation to physiological state. - Blomberg, A (1988)
The importance of the physiological state of a culture of Saccharomyces cerevisiae for tolerance to sudden osmotic dehydration was studied, and it was investigated whether specific osmotolerance factors were demonstrable. The microcalorimeter was used to monitor growth, and different physiological states of the culture were selected and their osmotolerance was tested. In addition to cells in the stationary phase, cells from the transition phase between respirofermentative and respiratory catabolism were osmotolerant. S. cerevisiae exhibited ever-changing metabolism during batch growth on either glucose or ethanol as the carbon source. Instantaneous heat production per biomass formation (dQ/dX) and specific activity of sn-glycerol 3-phosphate dehydrogenase (GPDH) (EC 1.1.1.8) were shown to differ for different physiological states. Neither high respiratory activity nor low total cellular activity, nor factors involved in osmoregulation, i.e., intracellular glycerol or activity of GPDH, correlated with the osmotolerant phenotype.